The putative P‐gp inhibitor telmisartan does not affect the transcellular permeability and cellular uptake of the calcium channel antagonist verapamil in the P‐glycoprotein expressing cell line MDCK II MDR1. Issue 4 (11th June 2015) - Saaby, Lasse; Tfelt‐Hansen, Peer; Brodin, Birger
Abstract Verapamil is used in high doses for the treatment of cluster headache. Verapamil has been described as a P‐glycoprotein (P‐gp, ABCB1) substrate. We wished to evaluate in vitro whether co administration of a P‐gp inhibitor with verapamil could be a feasible strategy for increasing CNS uptake of verapamil. Fluxes of radiolabelled verapamil across MDCK II MDR1 monolayers were measured in the absence and presence of the putative P‐gp inhibitor telmisartan (a clinically approved drug compound). Verapamil displayed a vectorial basolateral‐to‐apical transepithelial efflux across the MDCK II MDR1 monolayers with a permeability of 5.7 × 10−5 cm sec−1 compared to an apical to basolateral permeability of 1.3 × 10−5 cm sec‐1. The efflux could be inhibited with the P‐gp inhibitor zosuquidar. Zosuquidar (0.4 μmol/L) reduced the efflux ratio (PB‐A/PA‐B) for verapamil 4.6–1.6. The presence of telmisartan, however, only caused a slight reduction in P‐gp‐mediated verapamil transport to an efflux ratio of 3.4. Overall, the results of the present in vitro approach indicate, that clinical use of telmisartan as a P‐gp inhibitor may not be an effective strategy for increasing brain uptake of verapamil by co‐administration with telmisartan.